Ответ:
1) а) (x+4)^2=x^2+8x+16
б) (y-5x)^2=y^2-10yx+25x^2
в) (3a-2)(3a+2)=9a^2-4
г) (c-2b)(c+2b)=c^2-4b^2
2) a) x^2-81=(x-9)(x+9)
б) y^2-4y+4=(y-2)^2
3) (c+6)^2-c(c+12)=c^2+12c+39-c^2-12c=36
4) a) (x+7)^2-(x-4)(x+4)=65
x^2+14x+49-x^2+16-65=0
14x=0
x=0
б) y^2-
=0
y^2=![\frac{49}{64} \frac{49}{64}](https://tex.z-dn.net/?f=%5Cfrac%7B49%7D%7B64%7D)
y=±![\sqrt{\frac{49}{64} } \sqrt{\frac{49}{64} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B49%7D%7B64%7D%20%7D)
y=±![\frac{7}{8} \frac{7}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B8%7D)
5) a) (4a^2+b^2)(4a^2-b^2)=(16a^4-b^4)
б) (m+2n)(m-2n)=m^2-4n^2 (из первой скобки вынесли "2")
6) а) 36x^4y^2-169c^4=(6x^2y-13c^4)(6x^2y+13c^4)
в) (x+1)^2-(x-1)^2=(x+1-x+1)(x+1+x-1)=2(2x)=4x